2013
DOI: 10.3354/meps10460
|View full text |Cite
|
Sign up to set email alerts
|

Fish predation after weakly synchronized larval release in a coastal upwelling system

Abstract: Timing of larval release by many shore crabs is cued by environmental cycles to occur during nocturnal spring ebb tides, when larvae are transported away from high densities of planktivorous fishes in the dark. However, a recent laboratory study indicated that larval release may be weakly synchronized relative to this safe period in upwelling regions, potentially increasing fish predation. We determined the timing of larval release and predation in marshes in an upwelling region by sampling plankton and fishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Potential lingering scent after the removal of predators in our flow-through tanks was not an issue because results were similar in predator and control treatments. Further, larval release during late ebb tide was also common during our field experiment as well as a companion study in natural populations (Rasmuson and Morgan, 2013). Finally, a previous study also concluded that behaviors of P. crassipes are not altered simply by holding them in the laboratory (Bovbjerg, 1960).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Potential lingering scent after the removal of predators in our flow-through tanks was not an issue because results were similar in predator and control treatments. Further, larval release during late ebb tide was also common during our field experiment as well as a companion study in natural populations (Rasmuson and Morgan, 2013). Finally, a previous study also concluded that behaviors of P. crassipes are not altered simply by holding them in the laboratory (Bovbjerg, 1960).…”
Section: Discussionmentioning
confidence: 67%
“…In a companion study, predation was indeed highest on newly released larvae of P. crassipes and other shore crabs when larval release peaked away from the safe period (intermediate amplitude ebb tides in twilight; Rasmuson and Morgan, 2013). However, predation was not as high as expected, because planktivorous fishes were not always present while females were releasing larvae.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations